(untitled) (Research, Society and Development, 2023)
Admissions for Conditions Sensitive to Primary Care (ICSAP) are indicators of the level of resolution of actions carried out in Primary Care, especially those focused on the prevention of preventable diseases and injuries. The study aims to identify the rate and trend of ICSAP in adolescents in the 52 municipalities of Rondônia, from 2008 to 2019. This is an ecological time series study, with secondary data from the Hospital Information System, organized by age group (10-14 years; 15-19 years) and groups by diseases and health regions, with exposure of interest and cause of hospitalization. In the analysis, Microsoft Excel ® and STATA® version 16.9 programs and linear regression were used, applying the Prais-Winsten technique. The highest rate of ACSC was due to infectious gastroenteritis and complications (20.17/10,000), respiratory diseases (14.04/10,000), kidney/urinary tract infection (35.56/10,000) and conditions related to pre-christmas/childbirth (12.24/10 thousand). The lowest rates of ACSC were due to diseases preventable by immunization/ sensitive conditions, in both age groups (3.09/10,000 and 3.50/10,000), with a stable trend, signaling gaps in vaccination coverage. ACSC associated with prenatal care/childbirth had the highest annual growth (10.57%), followed by skin/subcutaneous tissue infections (14.50%) and epilepsy (5.58%). It is concluded that ICSAP in adolescents in the State of Rondônia remain neglected, exposing serious flaws in the line of care. Thus, it is urgent to strengthen intersectoral partnerships (health/education), prioritizing surveillance and promotion of adolescent health in primary care.